Isoflurane Enhances the Moonlighting Activity of GAPDH: Implications for GABAA Receptor Trafficking. (17th October 2012) - Montalbano, Andrew J.; Theisen, Christopher S.; Fibuch, Eugene E.; Seidler, Norbert W.
Abstract : GABA A receptor activity is directly modulated by glyceraldehyde 3-phosphate dehydrogenase (GAPDH), a protein with many nonglycolytic moonlighting functions. In addition to playing a role in the phosphorylation of the receptor, GAPDH may also participate in proper receptor trafficking to the plasma membrane. We previously showed that volatile anesthetics affect GAPDH structure and function that may contribute to the manner by which GAPDH modulates the GABA A receptor. In the current study, GAPDH interacted with engineered phospholipid-containing vesicles, preferring association with phosphatidylserine over phosphatidylcholine. Phosphatidyl-serine is known to participate in membrane trafficking of transport proteins and to play a role in GABA A receptor stability and function. We observed that GAPDH promoted the self-association and fusion of phosphatidyl-serine-rich vesicles as well as decreased membrane fluidity. Isoflurane enhanced each of these GAPDH-mediated events. Isoflurane also increased the binding of GAPDH to the cytoplasmic loop of the GABA A receptor. These observations are consistent with the working model of isoflurane playing a role in the trafficking of membrane proteins. This study is the first to implicate GAPDH and isoflurane in the regulation of GABA A receptor localization, providing insight into the mechanism of action of anesthesia.